2014
DOI: 10.1116/1.4904206
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of ultrathin blocking layer for low-temperature solid oxide fuel cell on nanoporous substrate

Abstract: An ultrathin yttria-stabilized zirconia (YSZ) blocking layer deposited by atomic layer deposition (ALD) was utilized for improving the performance and reliability of low-temperature solid oxide fuel cells (SOFCs) supported by an anodic aluminum oxide substrate. Physical vapor-deposited YSZ and gadolinia-doped ceria (GDC) electrolyte layers were deposited by a sputtering method. The ultrathin ALD YSZ blocking layer was inserted between the YSZ and GDC sputtered layers. To investigate the effects of an inserted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…Consequently, the cell with the ALD CeO 2 -coated cathode shows a very high peak power density of 800 mW cm –2 at an even more elevated temperature of 500 °C, which is the record-high performance among nanoporous-substrate-based thin-film SOFCs reported at this temperature range (≤500 °C) (Figure and Figure S11). ,,, Compared to the performances of nanoporous substrate-supported LT-SOFCs reported previously, which are mostly ≤400 mW/cm 2 at the temperature range of ≤500 °C, the LT-SOFC of this work demonstrates a high power density that is close to that of high-temperature SOFCs (∼1 W/cm 2 ), and it is easily scalable due to the use of nanoporous substrates as well as batch thin-film processes.…”
Section: Resultsmentioning
confidence: 72%
“…Consequently, the cell with the ALD CeO 2 -coated cathode shows a very high peak power density of 800 mW cm –2 at an even more elevated temperature of 500 °C, which is the record-high performance among nanoporous-substrate-based thin-film SOFCs reported at this temperature range (≤500 °C) (Figure and Figure S11). ,,, Compared to the performances of nanoporous substrate-supported LT-SOFCs reported previously, which are mostly ≤400 mW/cm 2 at the temperature range of ≤500 °C, the LT-SOFC of this work demonstrates a high power density that is close to that of high-temperature SOFCs (∼1 W/cm 2 ), and it is easily scalable due to the use of nanoporous substrates as well as batch thin-film processes.…”
Section: Resultsmentioning
confidence: 72%
“…The EIS curve for the Cell-B contains two predominant semicircles with peak imaginary values at 1 kHz and at 20 Hz by a non-linear least square fitting to the equivalent circuit consisting of one resistance (related to ohmic resistance) and two pairs of constant phase element and resistance (related to electrode–electrolyte interfacial resistance) [6]. Referring to the previous literatures [6,2022], it is considered that semicircles at higher and lower frequencies correspond to the anode and cathode interfacial resistances, respectively. The Cell-A, on the other hand, shows the EIS behavior with a diagonal form at a lower frequency region below 20 Hz, which is not observed in the impedance spectra of Cell-B.…”
Section: Resultsmentioning
confidence: 99%
“…However, the cell performance was very low (<1 mW cm −2 at 550°C) due to physical defects induced by the chemical etching process leading to chemical shorting through the electrolyte. ALD YSZ electrolytes on a nanoporous substrate ALD thin films have also been widely employed as dense electrolytes for nanoporous substrates (e.g., anodized aluminum-oxide (AAO))-based MEA designs [59][60][61][62][63][64][65][66][67][68][69][70][71]. In 2011, ALD Al 2 O 3 , which is not an ionic conductor, was used to fabricate gas-tight electrolytes by physically filling pinholes and voids.…”
Section: Ald Ysz For 3d Structured Electrolytesmentioning
confidence: 99%
“…In addition, the anode structure was stabilized [64]. Cha's group reported the use of an ALD YSZ layer at the anode to impede reduction of doped CeO 2 (GDC or YDC) at elevated temperature [60,61,70,71]. By adopting the ALD YSZ layer, the OCV increased from ∼0.3 V to >1.0 V. Hong et al reported anodized aluminum oxide (AAO)-based SOFCs with a 180 nm layer of YSZ electrolyte fabricated by ALD [62].…”
Section: Ald Ysz For 3d Structured Electrolytesmentioning
confidence: 99%